2015
DOI: 10.1038/cddiscovery.2015.17
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin induces crosstalk between autophagy and apoptosis mediated by calcium release from the endoplasmic reticulum, lysosomal destabilization and mitochondrial events

Abstract: Curcumin, a major active component of turmeric (Curcuma longa, L.), has anticancer effects. In vitro studies suggest that curcumin inhibits cancer cell growth by activating apoptosis, but the mechanism underlying these effects is still unclear. Here, we investigated the mechanisms leading to apoptosis in curcumin-treated cells. Curcumin induced endoplasmic reticulum stress causing calcium release, with a destabilization of the mitochondrial compartment resulting in apoptosis. These events were also associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
131
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(148 citation statements)
references
References 51 publications
16
131
1
Order By: Relevance
“…However, curcumin has been recognized mainly as an anti-oxidant compound353637. In accordance, a recent study by Moustapha et al 38. revealed that this is the predominant effect at very low doses of curcumin (lower than 1 μM) while at higher concentrations, 10 μM, it starts inducing early events of autophagy and at even higher dosages (>25 μM) it induces apoptosis and endoplasmic reticulum stress causing calcium release, with destabilization of the mitochondrial compartment and promoting tumor cell death3839.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…However, curcumin has been recognized mainly as an anti-oxidant compound353637. In accordance, a recent study by Moustapha et al 38. revealed that this is the predominant effect at very low doses of curcumin (lower than 1 μM) while at higher concentrations, 10 μM, it starts inducing early events of autophagy and at even higher dosages (>25 μM) it induces apoptosis and endoplasmic reticulum stress causing calcium release, with destabilization of the mitochondrial compartment and promoting tumor cell death3839.…”
Section: Discussionmentioning
confidence: 80%
“…revealed that this is the predominant effect at very low doses of curcumin (lower than 1 μM) while at higher concentrations, 10 μM, it starts inducing early events of autophagy and at even higher dosages (>25 μM) it induces apoptosis and endoplasmic reticulum stress causing calcium release, with destabilization of the mitochondrial compartment and promoting tumor cell death3839. This hormetic characteristic of curcumin has been detailed using a tumor cell line namely, hepatocellular carcinoma Huh-7 cells38. Nonetheless, molecular effects of curcumin on complex cell systems might most likely be cell-type specific in a concentration and time-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…69. More detailed explanations are given in supplementary Materials and methods for cathepsins and calpain, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Curcumin can also be excited at 488 nm, with a lower fluorescent yield emission in the 500-530 nm range, for detection by flow cytometry and confocal microscopy. Curiously, this has rarely been used for curcumin imaging at the cellular level (8,9). Curcumin is a hydrophobic molecule with a log P value of 3.0 at neutral pH (10).…”
Section: Curcumin | Cell Death | Autophagy | Apoptosis | Ros | Calciumentioning
confidence: 99%
“…In this regard, the depletion of glutathione suggests that curcumin could act as a pro-oxidant contributor in some conditions (17). At low concentrations, curcumin reacts as an antioxidant, but acquires pro-oxidant properties above 20 µM, thus revealing its hormetic behavior (8,18). Curcumin is a pleiotropic molecule which interacts with multiple targets involved in inflammatory reactions, such as tumor necrosis factor-alpha (TNFα) and interleukins (ILs) (19).…”
Section: Curcumin | Cell Death | Autophagy | Apoptosis | Ros | Calciumentioning
confidence: 99%